Determinação de chumbo em tubos de raios catódicos e em solo contaminado por espectrometria de absorção atômica - Lima, Luiz Rogerio Monteiro [UNESP] (2014)
In this paper methods for the determination of lead in glass from cathode ray tube (CRT) and soil pipes contaminated by this type of waste were employed. Small parts of components CRT (television and computer) from different manufacturers were used and dismantled manually for analysis. After grinding, the vitreous samples were analyzed by SEM, EDS and XRD to determine the particle size and the elemental composition of the investigated material. For this study a mixture ratio of 1:1:1:4 by weight (electron gun, neck, funnel and screen) was used. For the analyzes by atomic absorption spectrometry in graphite furnace (GFAAS) samples were digested in acid medium ( HCl 2,4 mL, 1,2 mL HNO 3 , 2,4 mL HF and 2,0 mL of H 2 O) where about 125 mg of the glassy sample was added in PTFE bottle from the quantification was performed using the method of addition of analyte. . The total concentration of lead in CRTs was determined by GFAAS and the value for two mixtures from different samples were 735, 52 ± 6, 12 mg.kg -1 and 886.61 ± 5, 49 mg.kg -1 . The toxicity of the sample was assessed using the norm ABNT NBR 10004:2004 solid waste. The mixture was subjected to leaching tests and the leaching extract was analyzed by optical emission spectrometry with inductively coupled plasma (ICP OES) and atomic absorption spectrometry in flames (FAAS). The results indicated that about 85% of Pb present in the leach residue. The leaching tests performed for waste CRTs reached values of Class I (hazardous waste) in compliance with norm ABNT NBR 10004:2004, due to the high concentration of lead present in their composition. The danger of the glass was determined using Toxicity Characteristic leashing Procedure ( TCLP ) ( SW- 846 Method 1311 , USEPA 2003) , which determines the toxicity of waste by leaching . Waste CRTs were used in the simulation of improper disposal in soil and lettuce cultivation in contaminated ...